No Effect of the IGF-1 Gene rs35767 and rs17032362 Polymorphisms in the Etiology of Idiopathic Short Stature - Tekcan, D.; Baş, F.; Atalar, F.; Aydın, B. K.; Akan, G.; Tarhan, T.; Bundak, R.; Darendeliler, F. (Experimental and Clinical Endocrinology & Diabetes, 2012)
Idiopathic short stature (ISS) refers to pathophysiologically wide and heterogeneous range of disorders, which are considered to involve defects in growth hormone (GH) insulin like growth factor-1 (IGF-1) axis. This study was designed to evaluate GH- IGF-1 axis and investigate IGF-1 gene polymorphisms in ISS.108 patients with a mean age of 11.7±3.6 years constituted the study group, while 108 age and gender matched children with normal stature constituted the control group. Serum IGF-1 and insulin-like growth factor binding protein-3 (IGFBP-3) levels and two polymorphisms in IGF-1 gene (rs35767, rs17032362) were investigated.While mean IGF-1 SDS value was lower in study group (p=0.002), no difference was detected between mean IGFBP-3 SDS values. The IGF-1 gene rs35767 polymorphism genotype distribution did not exhibit a statistical difference between study (7.1% wild type, 29.6% heterozygous, 63.3% homozygous) and control groups (3.8% wild type, 39.6% heterozygous, 56.6% homozygous). IGF-1 gene rs17032362 polymorphism genotype distribution was not significantly different either between study (94.8% wild type, 5.2% heterozygous, 0% homozygous) and control groups (97.2% wild type, 2.8% heterozygous, 0% homozygous). Comparing the cases with wild type, homozygous and heterozygous carriers for both polymorphisms with respect to height, weight, BMI, IGF-1 and IGFBP-3 SDS values, no significant difference was detected.IGF-1 SDS levels of patients with ISS were significantly lower compared to control group. There was no difference between IGFBP-3 SDS levels. No effect of IGF-1 gene rs35767 and rs17032362 polymorphisms on stature, IGF-1 and IGFBP-3 levels could be demonstrated.
Keywords: short stature; growth hormone; IGF-1; IGFBP-3